Intestinal stenosis of Garré following emergency ventral hernia repair. Issue 8 (15th August 2021) - Padgett, Bethany; Gurung, Deborah; Seretis, Charalampos; Selvam, Lourdusamy
Abstract: Intestinal stenosis of Garré can occur as a result of prolonged ischemia after all types of hernia surgery. Abstract : Intestinal stenosis of Garré can occur as a result of prolonged ischemia after all types of hernia surgery.